PERAN CSR, UKURAN PERUSAHAAN, KARAKTER EKSEKUTIF DAN KONEKSI POLITIK TERHADAP POTENSI TAX AVOIDANCE - Mamlu Atul Munawaro; Ramdany Ramdany (STIE Muhammadiyah Jakarta, 2020)
The purpose of this research is to test the influence of corporate social responsibility, firm size , character executive and connections political about the potential of tax avoidance. The population in this research is a conglomerate company listed on the Indonesia Stock Exchange from 2014 to 2018. Sampling using the Purposive sampling method as much as 42 conglomerate companies in 2014-2018. The analytical techniques used in this study are multiple linear regression analyses. The results of the analysis showed that political connections were significantly positive against the potential tax avoidance. While Corporate Social Responsibility, corporate size, executive character are not determine the potential of tax avoidance.